Hubungan Motivasi Dengan Keterampilan Futsal Remaja Putri SMA N 1 Kinali Kabupaten Pasaman Barat - HERLISA, MARLIA; M Indika, Pudia; Septri; Pery Fajri, Hadi (Jurnal IKEOR, 2024)
Abstract: Background: Finding out how teenage girls' motivation and futsal ability relate to one another at SMA N 1 Kinali in West Pasaman Regency was the aim of this research. Motivation is a physiological and psychological state that encourages a person to take certain actions in order to fulfil needs or achieve goals. In life, motivation is very important, especially in sports, especially futsal. Due to the rarity of women playing futsal, The motivation of teenage girls who play futsal is a topic of interest for researchers. To see this drive, an assessment of futsal playing skills must be carried out. Method: This quantitative research uses a descriptive correlational approach with a sample size of 10 people. Tests of futsal playing skills are used to measure the dependent variable, which has passed validity and reliability tests, while questionnaires are used to examine the independent variable. Results: Ten respondents were given the questionnaire, and the skills test was administered according to the test protocol. Then, the statistical data was analysed using SPSS and product moment correlation. Following data processing and analysis, it was shown that none of the players exhibited really low motivation. 60% of the players had sufficient motivation, 20% had adequate motivation, 20% had deficient motivation, and 0% had great motivation. Based on the skill test results, 0 players (0%) were considered excellent, 6 players (60%) were considered good, 2 players (20%) were considered fair, 2 players (20%) were considered deficient, and 0 players (0%) were considered very deficient. As a result, it is concluded that the SMA N 1 Kinali female futsal players have a Good level of talent.